Subsurface drainage for slope stabilization - Forrester, Kevin 1927- (American Society of Civil Engineers, 2001)
A veteran civil engineer who worked with the Department of Main Roads in New South Wales for many years shares his expertise on the "landslides game." Forrester provides guidelines on: recent field practices and lab analysis methods for improving slope stability, in the geotechnical context of the mechanics of water flow through soil, rock, pipes, and other matter; filtration theory; filter design; and drain construction and performance assessment. Appends a ten- step field test for dissolved ferrous iron, and case examples for geotechnical practitioners and students working in subsurface drainage.